An investigation on parenting stress of children with cystic fibrosis - Grazia Isabella Continisio; Nicola Serra; Assunta Guillari; Maria Teresa Civitella; Angela Sepe; Silvio Simeone; Gianpaolo Gargiulo; Silvia Toscano; Maria Rosaria Esposito; Valeria Raia; Teresa Rea (BMC, 2020)
Abstract Background The management of chronic diseases, particularly in children, requires an integrated physical and psychological approach to both sick children and their family. This is the case of Cystic Fibrosis (CF), a complex genetic chronic disease, where, a comprehensive evaluation of the emotional impact and an effective multidimensional approach are indicated. Aim This study investigates on parenting stress in children and adolescents with CF and its determinants related to parents, children and the disease severity. Methods The study involved 34.04% adult males and 65.96% adult females (range 21-55 years) and 47 children with CF, 54.35% males and 45.65% females (range 1-17 years). The data were obtained through a Parenting Stress Index - Short Form (PSI-SF) questionnaire. According to the PSI-SF scoring system, three types of stress were detected: a typical stress pattern (normal), a high stress pattern (increased) and a defensive response, which may be considered as a high stress feature in children which requires monitoring and clinical evaluation. Results This study shows a significant presence of stress in females (60.23%), of subject married (84.62%), unemployed (69.23%) and with education level such as "middle School" (61.54%). Concerning children of parents with high stress, it resulted most frequent children with one sibling (53.85%). Finally, by univariate analysis, it resulted a significant positive correlation between parenting stress and disease degree of children. Instead by multivariate analysis, we found that the variables: Number of siblings and Birth order were a significant positive and negative predictor of parenting stress respectively. Conclusion An increased stress level was detected in less than one third of parents of subjects with CF. These data may be related to the psychological support which is part of the routine management of CF care team. However, as children's features seem to act as a determinant of stress more than parental ones, the parental-child dysfunction should be the target for further integrated interventions.